THE EFFECT OF LEVERAGE ON FIRM VALUE WITH DIVIDEND POLICY AS MODERATING IN BANKING COMPANIES LISTED ON THE STOCK EXCHANGE - Imam Nur Hidayat; Bambang Haryadi (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2022)
This paper means to analyze the impact of influence on the worth of the organization's profit strategy as an arbitrator in financial organizations recorded on the IDX. The insightful strategy utilized is Multiple Linear Regression Analysis. This investigation utilizes optional information got from yearly reports, banking fiscal summaries. Tests were completed on 23 financial organizations recorded on the IDX in 2014-2018. Influence utilized the Debt to Equity Ratio (DER), and the Dividend Policy utilized the Dividend Payout Ratio (DPR). The reliant variable in this investigation is firm worth which is proxied utilizing Tobin's Q. The outcomes acquired show that influence affects firm worth, profit strategy can direct the impact of influence on firm worth Of course this has a significant influence on the company's image so that the value of the company will rise and affect investor decisions.